Nutritional interventions for the management of frailty in older adults: systematic review and meta-analysis of randomized clinical trials - Moraes, Mariana B de [UNESP]; Avgerinou, Christina; Fukushima, Fernanda B. [UNESP]; Vidal, Edison I O [UNESP] (Oxford University Press (OUP), 2021)
CONTEXT: Although nutrition is considered an important intervention for the management of frailty, the actual effectiveness of interventions addressing nutrition in frail older people remains unclear. OBJECTIVE: The aim for this systematic review was to appraise the evidence regarding the effectiveness of nutritional interventions for the management of frailty in older adults. DATA EXTRACTION: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature, Cochrane Central Register of Controlled Trials, Web of Science, and Latin American and Caribbean Health Sciences Literature databases were searched from January 2001 to November 2019. Two independent reviewers extracted relevant data. From 2370 initial records, 19 publications presenting data from 17 studies (1564 individuals; follow-up: 7-96 weeks) were included. DATA ANALYSIS: None of the Bayesian random-effects meta-analyses comparing nutritional supplements with placebo regarding mortality, body mass index, weight, frailty status, muscle strength, gait speed, body composition, and cognitive function showed statistically significant differences. The same applies to a single meta-analysis comparing nutritional education with general health advice regarding muscle strength. CONCLUSION: Our results suggest, mostly with low to very low degrees of certainty, that nutritional supplements or nutritional education delivered in isolation may not be effective for the management of frailty in older people. REVIEW REGISTRATION NUMBER: CRD42018111510 (PROSPERO).
Keywords: aged; dietary supplements; frailty; meta-analysis; nutrition; systematic review